ORIGIN Trial Proves Safety of Insulin, Lack of Efficacy for n-3 Fatty Acids - Buckley, Rita (MD Conference Express, 2012)
This article presents an overview of the Outcome Reduction With an Initial Glargine Intervention Trial [ORIGIN; NCT00069784]. ORIGIN was a large, international, randomized, controlled trial that lasted >6 years in people with new or recently diagnosed diabetes, impaired fasting glucose, impaired glucose tolerance, and additional cardiovascular (CV) risk factors. ORIGIN is the longest investigation of the effect of insulin treatment on CV outcomes and cancer incidence in this population to date.